Departure Time Choice Analysis Using Ordered Response Probit Model: Journey to Work Trip in Dhaka City - Anwar, A H M Mehbub (Journal of Bangladesh Institute of Planners, 2012)
With growing concern about travel time increase and energy consumption, transportation planners and decision makers are becoming gradually more conscious of the necessary reallocation of the departure time at the peak period travel in an effort to reduce traffic congestion, environmental emission and peak load. The paper addresses this particular problem through the development and estimation of a journey to work (JTW) departure time choice model. The model has been developed by considering five characteristics, such as individual socio-demographics, household socio demographic characteristic, employment related attributes, trip related attributes and arrival related aspects. By identifying departure time choice, one can observe the level of earlier start as an ordinal variable that expresses extremity of earlier start behavior which is increased with larger values of departure time. To represent this ordinal variable, an ordered response probit (ORP) model has been employed to investigate the JTW trips in Dhaka city. Journal of Bangladesh Institute of Planners Vol. 5, Dec 2012, pp. 107-118